Implementasi Public Relations (PR) dalam meningkatkan citra angkringan Kopi Songo Pitu Kota Malang di masa mendatang - Susanto, Rosya Mawaddah (Maliki Interdisciplinary Journal, 2023)
In an organization Public Relations (PR) is one of the important things, because PR is a practice that manages the dissemination of information between individuals and organizations. PR actors are obliged to provide information, convince, gain sympathy and arouse public interest in something. PR activities are considered to be able to build and improve the image and identity of a company or organization. PR in the business world must have innovations that can foster public interest and introduce them to various products and advantages in the culinary field. One of them is Songo Pitu angkringan which certainly has advantages in its products and facilities. The purpose of this writing is to implement PR practices at Songo Pitu angkringan in order to improve the image of angkringan in the future. This article provides a discussion regarding the urgency, role and practice of public relations (PR) which includes PR activities, obstacles faced and solutions provided. Having PR practices will certainly provide better service to customers. This will certainly build a sense of comfort and customer satisfaction with the services provided. So with this comfort and satisfaction, it can grow and improve the image of Songo Pitu angkringan.